A conduta pedagógica perante o desenho nos anos iniciais: uma revisão integrativa (2017 a 2021) - Santiago, Andrea Maria de Moraes (2022)
This paper proposes to do a research with integrative review of articles published in Scielo platform, between the years 2017 and 2021, which address the pedagogical conduct before the drawing in the early years of elementary school. We can look at the history of Art Education in Brazil, and understand the difficulties of Art teachers in placing within the classroom the four languages that constitute this discipline (theater, music, visual arts and dance). Thus, Vigotskian studies provided the theoretical reference support for this dissertation. These studies raise the perception of the importance of art in child development. In this research it was possible to notice the reduced academic production in the area of "Art Education", "Art teaching", and "children's drawing", mainly regarding the initial years of elementary school. It is necessary to prioritize the training of Art teachers and encourage academic production in the area of Art Education in the early years to produce significant changes